2015
DOI: 10.1002/qj.2586
|View full text |Cite
|
Sign up to set email alerts
|

An analytic model of tropical cyclone wind profiles

Abstract: A physically based analytic model (λ model) is presented to describe the wind profile of the tropical cyclones in terms of the pressure deficit and a single shape parameter (λ).To test the λ model, an idealized full-physics numerical model is employed to provide

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 27 publications
(38 citation statements)
references
References 37 publications
(59 reference statements)
1
37
0
Order By: Relevance
“…The new WPR (Wang and Toumi, ) derived from the λ‐model (Wang et al, ) can be written as PminPenv=ρVmax+0.5foRmax_normalKZ070.772 where ρ is the air density set as 1.1 kg m −3 , P env the pressure in the ambient environment, f o the Coriolis parameter that depends on the TC location, and R max_KZ07 a proxy of R max for the pressure deficit (i.e. P min – P env ) estimation.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The new WPR (Wang and Toumi, ) derived from the λ‐model (Wang et al, ) can be written as PminPenv=ρVmax+0.5foRmax_normalKZ070.772 where ρ is the air density set as 1.1 kg m −3 , P env the pressure in the ambient environment, f o the Coriolis parameter that depends on the TC location, and R max_KZ07 a proxy of R max for the pressure deficit (i.e. P min – P env ) estimation.…”
Section: Methodsmentioning
confidence: 99%
“…Idealized model studies (e.g. Chan and Chan, ; Wang et al, ) showed the decaying of intensity and increase in size after maturity but did not link them. These changes are independent of experimental design in the simple numerical‐dynamical model (Ooyama, ) and state‐of‐art full‐physics numerical models.…”
Section: Introductionmentioning
confidence: 99%
“…An initial vortex with a rapid decrease in tangential winds with radius (such as that used in Sawada and Iwasaki 2010) will have a different response to heating compared with one that has a slow decrease (such as that used in Hill and Lackmann 2009). Wang et al (2015) used an idealized full-physics numerical model to show that high sea surface temperature (SST) is favorable to TC size growth. Higher SST gives a larger air-sea temperature contrast, and results in stronger latent energy transfer from the ocean to the air.…”
Section: Outer Windsmentioning
confidence: 99%
“…DeMaria and Pickle 1988;Li et al 2012). Second, TC size decreases with increasing f (e.g., Chavas and Emanuel 2014;Wang et al 2015). Third, TC has an optimum latitudinal region for TC size growth (e.g., Smith et al 2011;Chan 2014, 2015a).…”
Section: Planetary Vorticitymentioning
confidence: 99%
See 1 more Smart Citation